Alpha Phi-shing Fraternity: Phishing Assessment in a Higher Education Institution - Marco Casagrande; Mauro Conti; Monica Fedeli; Eleonora Losiouk (Journal of Cybersecurity Education, Research & Practice, 2023)
Phishing is a common social engineering attack aimed to steal personal information. Universities attract phishing attacks because: 1) they store employees and students sensitive data, 2) they save confidential documents, 3) their infrastructures often lack security. In this paper, we showcase a phishing assessment at the University of Redacted aimed to identify the people, and the features of such people, that are more susceptible to phishing attacks. We delivered phishing emails to 1.508 subjects in three separate batches, collecting a clickrate equal to 30%, 11% and 13%, respectively. We considered several features (i.e., age, gender, role, working/studying field, email template) in univariate and multivariate analyses and found that students are more susceptible to phishing attacks than professors or technical/administrative staff, and that emails designed through a spearphishing approach receive a highest clickrate. We believe this work provides the foundations for setting up an effective educational campaign to prevent phishing attacks not only at the University of Redacted, but in any other university.